Chemogenetic emulation of intraneuronal oxidative stress affects synaptic plasticity - Kalinichenko, Andrei L.; Jappy, David; Solius, Georgy M.; Maltsev, Dmitry I.; Bogdanova, Yulia A.; Mukhametshina, Liana F.; Sokolov, Rostislav A.; Moshchenko, Aleksandr A.; Shaydurov, Vladimir A.; Rozov, Andrei; Podgorny, Oleg V.; Belousov, Vsevolod V. (Redox Biology, 2023)
Oxidative stress, a state of disrupted redox signaling, reactive oxygen species (ROS) overproduction, and oxidative cell damage, accompanies numerous brain pathologies, including aging-related dementia and Alzheimer's disease, the most common neurodegenerative disorder of the elderly population. However, a causative role of neuronal oxidative stress in the development of aging-related cognitive decline and neurodegeneration remains elusive because of the lack of approaches for modeling isolated oxidative injury in the brain. Here, we present a chemogenetic approach based on the yeast flavoprotein d-amino acid oxidase (DAAO) for the generation of intraneuronal hydrogen peroxide (H2O2). To validate this chemogenetic tool, DAAO and HyPer7, an ultrasensitive genetically encoded H2O2 biosensor, were targeted to neurons. Changes in the fluorescence of HyPer7 upon treatment of neurons expressing DAAO with d-norvaline (D-Nva), a DAAO substrate, confirmed chemogenetically induced production of intraneuornal H2O2. Then, using the verified chemogenetic tool, we emulated isolated intraneuronal oxidative stress in acute brain slices and, using electrophysiological recordings, revealed that it does not alter basal synaptic transmission and the probability of neurotransmitter release from presynaptic terminals but reduces long-term potentiation (LTP). Moreover, treating neurons expressing DAAO with D-Nva via the patch pipette also decreases LTP. This observation indicates that isolated oxidative stress affects synaptic plasticity at single cell level. Our results broaden the toolset for studying normal redox regulation in the brain and elucidating the role of oxidative stress to the pathogenesis of cognitive aging and the early stages of aging-related neurodegenerative diseases. The proposed approach is useful for identification of early markers of neuronal oxidative stress and may be used in screens of potential antioxidants effective against neuronal oxidative injury.
Online verfügbar 10 January 2023, Version des Artikels 12 January 2023
Gesehen am 07.08.2023